Green synthesis of alumina nanoparticle using Hibiscus rosa-sinensis leaf extract as a candidate for molybdenum-99 adsorbent. (March 2023) - Marlina,; Yanto,; Triyatna, F.; Lestari, E.; Sarmini, E.; Mujamilah,; Awaludin, R.; Yulizar, Y.
Abstract: Al2 O3 nanoparticle is effectively used as an adsorbent for the low specific activity of molybdenum-99 ( 99 Mo). The Al2 O3 nanoparticle was synthesized by the green synthesis method using Hibiscus rosa-sinensis leaf extract (HRE). The Al2 O3 nanoparticle synthesized using 10% of the HRE has a crystallite size of 4.9 nm, a surface area of 254.6 m 2 /g, a pore size of 9.1 nm, a pore volume of 0.58 cm 3 /g and has a Mo adsorption capacity of 43.4 ± 6.1 mg Mo/g. Highlights: Al2 O3 nanoparticle was prepared by using Hibiscus rosa-sinensis leaf extract (HRE). The alkaloid content in the HRE as a base source for the hydrolysis reaction. The other secondary metabolites in the HRE have a role as capping agents, stabilizers, or templates. The synthesized Al2 O3 nanoparticle was used as a molybdenum-99 ( 99 Mo) adsorbent.